Pilot scale production of dessicated coconut (DCN) cookies - Manguerra, Ethel C.; Dumelod, Benelyn Domingo (1995.)
This study aimed at producing desiccated coconut cookies (DCN) on a pilot-scale in an attempt to increase dietary fiber intake by providing a more accessible source. Phase I involved the translation to pilot-scale production of a bench-scale standardized formulation of DCN cookies. Raw material specifications and quality control points were established based on two batches of pilot-scale production. In Phase II, the cookies from Phase I were tested for reproducibility in terms of sensory properties, microbial load, proximate composition and coat. Test for difference between mean sensory scores for color, flavor, texture and general acceptability of DCN cookies from batches I and II of pilot-scale production showed no significant difference. Microbial load of both batches were within limits for cookies. Percent composition of cookies from batch I was slightly higher than that of batch I was slightly higher than that of batch II except for crude fat. Unit cost was P0.65. In Phase III, effect of upscaling was determined by comparing results of bench-scale production done by Gasapos (1995) with those of pilot scale production. No significant differences existed between sensory attributes of the cookies from two production levels except for texture. This, however proved to be favorable. The microbial load of both production levels were within limits. The proximate composition of cookies from pilot-scale production was slightly higher than that of bench-scale produce except for total available carbohydrates and ash. Unit cost was 33% lower in pilot-scale production than in bench-scale production.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Cookies; Coconut products